Pengaruh Etika Profesi, Tingkat Pendidikan dan Pengalaman Kerja Terhadap Kinerja Auditor Pada Badan Pengawasan Keuangan Dan Pembangunan (BPKP) Sumatera Utara - Mercy Grace Kartika Sari Zagoto; Keumala Hayati (Universitas Batanghari, 2020)
The auditor's performance is a benchmark of failure or success of the duties and responsibilities given in examining financial statements. To achieve the success of the auditor's performance, of course it is influenced by several factors. Therefore, from this study, it can be known that Professional Ethics, Education level and Work Experience affect the performance of auditors in BPKP North Sumatra. This research is conducted so that each auditor can carry out their duties and responsibilities in accordance with ethics and laws so that there is no cheating. In sampling, simple random sampling method is used which means that in the selection of samples is conducted randomly that as many as 125 questionnaires are spread and that returns only 100 questionnaires. To analyze the data is to use multiple linear regression analysis. The results of this study show that professional ethics, education level and work experience have a simultaneous effect on the performance of auditors in BPKP North Sumatra. Partially Professional Ethics and Education Level does not affect the performance of auditors. While the effect on the performance of auditors is only variables only work experience.